Cinacalcet in peritoneal dialysis patients: one-center experience - Conde,Sara Querido (2017)
Abstract Introduction: Secondary hyperparathyroidism is the target of several therapeutic strategies, including the use of cinacalcet. Most studies were done only in hemodialysis patients, with few data from peritoneal dialysis patients. Objective: The aim of our work was to evaluate the effectiveness of cinacalcet in secondary hyperparathyroidism in a one-center peritoneal dialysis patients. Methods: A retrospective study was performed in 27 peritoneal dialysis patients with moderate to severe secondary hyperparathyroidism (PTHi > 500 pg/mL with normal or elevated serum calcium levels) treated with cinacalcet. Demographic, clinical and laboratory parameters at the beginning of cinacalcet therapy, second, fourth, sixth months after and at the time it was finished were analyzed. Results: Patients were under peritoneal dialysis at 30.99 ± 16.58 months and were treated with cinacalcet for 15.6 ± 13.4 months; 21 (77.8%) patients showed adverse gastrointestinal effects; PTHi levels at the beginning of cinacalcet therapy were 1145 ± 449 pg/mL. The last PTHi levels under cinacalcet therapy was 1131 ± 642 pg/mL. PTHi reduction was statistically significant at 2 months after the beginning of cinacalcet (p = 0.007) but not in the following evaluations. Conclusion: It is necessary the development of new forms of cinacalcet presentation, in order to avoid gastrointestinal effects adverse factors and to improve therapeutic adherence.